COMMUNITY DEVELOPMENT INFLUENCE ON PUBLIC'S KNOWLEDGE IN MANDANGIN ISLAND ABOUT ACUTE DIARRHEA AND FUNCTIONAL CONSTIPATION IN CHILDREN - Ranuh, Reza Gunadi; Susianto, Steven Christian; Athiyyah, Alpha Fardah; Darma, Andy; Puspitasari, Dwiyanti; Sumitro, Khadijah Rizky; Nesa, Ni Nyoman Metriani; Faizi, Muhammad; Sudarmo, Subijanto Marto (Universitas Airlangga, 2022)
In children, acute diarrhea and functional constipation (FC) are still more prevalent in Indonesia, especially in isolated islands, and need comprehensive management. This study aimed to determine the effect of community development from the Department of Child Health Faculty of Medicine, Universitas Airlangga, Surabaya, on Mandangin Island's public knowledge about acute diarrhea and functional constipation in children. This cross-sectional study was conducted on 29 subjects from Mandangin Island, Sampang, Indonesia on 17th February 2022. Subjects were given education and dissemination as community development by pediatricians via hybrid and could ask questions and discuss at the end of the presentation. The subject's knowledge was measured using a pre-and post-test questionnaire about children's acute diarrhea and functional constipation. Each questionnaire (diarrhea and functional constipation) consisted of 5 questions, with a minimum score of 0 and the maximum score of 100. The subject's knowledge was compared before and after the webinar using Paired T-Test and p<0,05 was measured as significant. We assessed the subject's age, gender, occupation, and last education. There was a significant increase in public knowledge about diarrhea (26,9±18,7; 55,1±24,3; p=0.000) and functional constipation pre-and post-webinar (24,8±18,2; 48,3±24,2; p=0.000). These findings support the importance of community development with education about acute diarrhea and functional constipation in children.